(untitled) (International Journal of Engineering and Computer Science, 2017)
Highways in India are different from other roads of the country. Traffic on Indian roads consists of a mix characteristic type of vehicles. These vehicles in the highway have widely different static and dynamic characteristics. Traffic is essentially consists of bicycles, two-wheelers, three-wheelers, Light commercial vehicle, cars and trucks this work aims to study of traffic flow on Indian highways by evaluating Passenger Car Unit (PCU) of different vehicle categories at different section of highwaysaround Nagpur city. Our aim is to work out the passenger car unit PCU for different types of vehicles under non homogeneous traffic conditions. Field data collection was conducted at four highway links and at outside of urban areas and the different types of vehicles in Non Homogeneous traffic, for a wide range of mix traffic volume and width of highways. This PCU is utilized to increase the area of shoulder linearly for free speed of a vehicle with width. I observed that from the study of traffic volume and roadway conditions that the PCU value of a vehicle significantly changes with change in volume of mix traffic and width of roadway. The capacity of highways also increases with use of shoulder area and its positive effect on PCU value for type of vehicle increases with increases lane width This is resulting due to the high proportion of the road space occupied (high area occupancy) by heavy vehicles even when less number of heavy vehicles are present on the road. Because of this, maximum PCE value for both trailer and truck is increasing at low proportions and remains constant at high proportion. The relationship between the volume and speed at different highway section developed a second-degree curve. This relationship is used to calculate capacity of highways.